2013
DOI: 10.1021/jp4005289
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Forces and Molecular Dynamics Simulation of 1,3,5-Triamino-2,4,6-trinitrobenzene (TATB) Using Symmetry Adapted Perturbation Theory

Abstract: The dimer potential energy surface (PES) of 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) has been explored using symmetry adapted perturbation theory based on a Kohn-Sham density functional theory description of the monomers [SAPT(DFT)]. An intermolecular potential energy function was parametrized using a grid of 880 ab initio SAPT(DFT) dimer interaction energies, and the function was used to identify stationary points on the SAPT(DFT) dimer PES. It is shown that there exists a variety of minima with a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The vertically arranged red dots denote a set of Lagrangian tracer particles embedded in the sample for the purpose of generating the t-z diagrams and temperature time histories mentioned above. 45, www.pep.wiley-vch.de pore shapes, pressure, stress, and temperature fields over this range of flow conditions. For a head-to-head comparison, postprocessing of the MD and continuum results is necessary to juxtapose them meaningfully and on an equal footing.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The vertically arranged red dots denote a set of Lagrangian tracer particles embedded in the sample for the purpose of generating the t-z diagrams and temperature time histories mentioned above. 45, www.pep.wiley-vch.de pore shapes, pressure, stress, and temperature fields over this range of flow conditions. For a head-to-head comparison, postprocessing of the MD and continuum results is necessary to juxtapose them meaningfully and on an equal footing.…”
Section: Methodsmentioning
confidence: 97%
“…The crystal is triclinic with two molecules per unit cell. The structure of the crystal is strongly anisotropic and this is reflected in pronounced anisotropy for many of the thermal [39][40][41][42][43][44][45][46][47][48][49][50], mechanical [51][52][53][54][55][56][57][58][59][60], and optical properties [61].…”
Section: Introductionmentioning
confidence: 99%
“…The additional difficulty is that TATB, like other energetic materials (see, for example, the recent work by Taylor 16 ), is a relatively "soft" material with elastic constants about a few GPa at zero pressure. It means that finding a minimum on the potential energy surface is quite complicated for such systems.…”
Section: A Determination Of Optimal Calculation Parametersmentioning
confidence: 99%
“…A great deal of work has been performed to understand the relationship between structure and irreversible volume expansion of pure TATB crystals and TATB‐based PBXs in the past years. It is reported that due to hydrogen bonded molecular sheets, TATB crystals have a graphitic‐like and layer‐shaped structure . Because of weaker van der Waals forces between the layers than hydrogen‐bonding force within its a‐b plane, the thermal expansion coefficient at the direction perpendicular to its a‐b plane (denoted as c direction) is higher than that at the a and b axes .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that due to hydrogen bonded molecular sheets, TATB crystals have a graphitic-like and layer-shaped structure. 12,13 Because of weaker van der Waals forces between the layers than hydrogen-bonding force within its a-b plane, the thermal expansion coefficient at the direction perpendicular to its a-b plane (denoted as c direction) is higher than that at the a and b axes. 14 Considerable research efforts have been undertaken to reveal the origin of irreversible expansion of TATB crystals and TATB-based PBXs.…”
Section: Introductionmentioning
confidence: 99%